2017
DOI: 10.1080/14764172.2016.1269928
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic wave therapy for cellulite, body shaping and fat reduction

Abstract: AWT is a safe treatment to improve cellulite appearance and reduce body circumferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 25 publications
2
36
1
10
Order By: Relevance
“…Other studies on noninvasive RF or laser treatments included 6‐20 treatment sessions (Harth et al, Lach et al, Mlosek et al, Manuskiatti et al, Wanitphakdeedecha et al). Targeted pressure energy studies for cellulite reduction included 6 sessions (Knobloch et al, Christ et al), 8 sessions (Schlaudraff et al Steinert et al Nassar et al), or 12 sessions (Hexsel et al). Suction‐based evidence then speaks about a minimum of 15 treatments (Kutlubay et al Gülec).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on noninvasive RF or laser treatments included 6‐20 treatment sessions (Harth et al, Lach et al, Mlosek et al, Manuskiatti et al, Wanitphakdeedecha et al). Targeted pressure energy studies for cellulite reduction included 6 sessions (Knobloch et al, Christ et al), 8 sessions (Schlaudraff et al Steinert et al Nassar et al), or 12 sessions (Hexsel et al). Suction‐based evidence then speaks about a minimum of 15 treatments (Kutlubay et al Gülec).…”
Section: Discussionmentioning
confidence: 99%
“…Nassar et al 23 showed that eight sessions of acoustic wave therapy over 4 weeks in 15 patients resulted in efficient improvement of body contour and cellulite appearance 3 months after treatment 21,22 Hexsel et al 25 also demonstrated that 12 sessions over 6 weeks was effective in reducing cellulite severity in 30 women at the 12‐week follow up. Aside from clinical outcome, the treatment also improved patients’ quality of life, and no serious adverse events were reported.…”
Section: Energy‐based Devices For Cellulitementioning
confidence: 99%
“…Acoustic wave treatment has been initially used to treat kidney stones [3] [4] and injuries in the musculoskeletal system and soft tissue [5] [6] [7]. The positive effects observed on skin and subcutaneous tissue after acoustic wave treatments led to be applied for cosmetic and aesthetic purposes [8].…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic wave is a non-invasive technique based on the propagation of mechanical waves into the tissues [8]. It stimulates local blood circulation, cell metabolism, self-regenerating processes [9] [10], and cell proliferation of collagen and elastin fibres [9] [10] [11], and lipolysis [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation